Learning from Our Mistakes: Public Management Reform and the Hope of Open Government. Issue 4 (3rd February 2020) - Ingrams, Alex; Piotrowski, Suzanne; Berliner, Daniel
Abstract: In public administration today, many new reform ideas mingle, offering new diagnoses of governmental problems and courses of action. But scholars have highlighted reasons why we should doubt the optimistic claims of reformists. A new set of policy tools called "open government" arrived nearly a decade ago, and scholars have not yet explained its origins or prospects as specific approach to management reform. In this article, we address this lacuna. We compare open government with three other historic reforms, and analyze how likely its ideas are to bear fruit. In so doing, we introduce a framework for evaluating risks inherent in any new reform approach. We conclude that the challenges faced by open government are both new and old, but—like all reform approaches—they result from management challenges in reconciling competing interests and values that raise tensions and can lead to unexpected consequences. We argue that these will need careful attention if the open government approach is to have any hope of succeeding.